Embelin and Its Derivatives: Design, Synthesis, and Potential Delivery Systems for Cancer Therapy - Michael Danquah (Pharmaceuticals, 2022)
Embelin is a naturally occurring benzoquinone that inhibits the growth of cancer cells, making it a potent anticancer drug. However, the low water solubility of embelin restricts its clinical applicability. This review provides a concise summary and in-depth analysis of the published literature on the design and synthesis of embelin derivatives possessing increased aqueous solubility and superior therapeutic efficacy. In addition, the potential of drug delivery systems to improve the anticancer capabilities of embelin and its derivatives is discussed.